Cost of inaction on sugar-sweetened beverage consumption: implications for obesity in South Africa. Issue 13 (23rd October 2015) - Tugendhaft, Aviva; Manyema, Mercy; Veerman, Lennert J; Chola, Lumbwe; Labadarios, Demetre; Hofman, Karen J
Abstract: Objective: To estimate the effect of increased sugar-sweetened beverage (SSB) consumption on future adult obesity prevalence in South Africa in the absence of preventive measures. Design: A model was constructed to simulate the effect of a 2·4 % annual increase in SSB consumption on obesity prevalence. The model computed the change in energy intake assuming a compounding increase in SSB consumption. The population distribution of BMI by age and sex was modelled by fitting measured data from the 2012 South African National Income Dynamics Survey to the log-normal distribution and shifting the mean values. Setting: Over the past decade the prevalence of obesity and related non-communicable diseases has increased in South Africa, as have the sales and availability of SSB. Soft drink sales in South Africa are projected to grow between 2012 and 2017 at an annual compounded growth rate of 2·4 % in the absence of preventive measures to curb consumption. Results: A 2·4 % annual growth in SSB sales alongside population growth and ageing will result in an additional 1 287 000 obese adults in South Africa by 2017, 22 % of which will be due to increased SSB consumption. Conclusions: In order to meet the South African target of reducing the number of people who are obese and/or overweight by 10 % by 2020, the country cannot afford to delay implementing effective population-wide interventions. In the face of plans to increase growth of SSB, the country will soon face even greater challenges in overcoming obesity and related non-communicable diseases.